Survey of typical Variable Structure Multi-models estimation algorithms - Liu Yang; Liu Huo-ping; Wu Qin-zhang (2010 International Conference on Computer, Mechatronics, Control and Electronic Engineering, 2010)
As a new branch of multi-models method, Variable Structure Multiple Models (VSMM) approach is a hot topic, which involves target tracking, fault detection, etc. In this paper, it analyzes VSMM method in depth, at first. Then, it introduces three kinds of essential idea of Model Set Adaptive (MSA) being the kernel of VSMM, respectively. In succession, three typical and practical algorithms of VSMM is reviewed and analyzed, at the same time, some new algorithms which are developed basing on the these algorithms mentioned above are summarized. At last, the paper points out some problems which are waiting for being solved in VSMM.